2009
DOI: 10.1093/bioinformatics/btp193
|View full text |Cite
|
Sign up to set email alerts
|

From disease ontology to disease-ontology lite: statistical methods to adapt a general-purpose ontology for the test of gene-ontology associations

Abstract: Subjective methods have been reported to adapt a general-purpose ontology for a specific application. For example, Gene Ontology (GO) Slim was created from GO to generate a highly aggregated report of the human-genome annotation. We propose statistical methods to adapt the general purpose, OBO Foundry Disease Ontology (DO) for the identification of gene-disease associations. Thus, we need a simplified definition of disease categories derived from implicated genes. On the basis of the assumption that the DO ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 17 publications
1
94
0
1
Order By: Relevance
“…We use the hypergeometric test to measure the statistical significance of the enrichment of a gene set S in a GO [2] or DO term t [8]. Now, E is the set of genes from StatNetExpression that are annotated by any GO/DO term, A is the subset of genes from S that are present in E, G is the subset of genes from E that are annotated by t, and O is the set of genes that are present in both A and G [9].…”
Section: Validating Aging-related Predictionsmentioning
confidence: 99%
“…We use the hypergeometric test to measure the statistical significance of the enrichment of a gene set S in a GO [2] or DO term t [8]. Now, E is the set of genes from StatNetExpression that are annotated by any GO/DO term, A is the subset of genes from S that are present in E, G is the subset of genes from E that are annotated by t, and O is the set of genes that are present in both A and G [9].…”
Section: Validating Aging-related Predictionsmentioning
confidence: 99%
“…pizzas or human diseases (Horridge et al, 2004;Du et al, 2009). In many research disciplines outside of taxonomy, it is epistemologically permissible to maintain multiple alternative hierarchies.…”
Section: Sections I To Iii -Epistemological Constraintsmentioning
confidence: 99%
“…It is suggested that GeneRIF-Disease Ontology (DO) mapping performs better than OMIM when the prediction performances are compared [23,24]. Mapping process is illustrated in Figure 6, where the association between Gene ID: 7040 and DO ID: 2585 is shown.…”
Section: Disease Datamentioning
confidence: 99%